An association study between MiR-146a and INSR gene polymorphisms and hypertensive disorders of pregnancy in Northeastern Han Chinese population. (15th January 2021) - Lu, Rui; Liu, Nana; Feng, Xiu; Feng, Yanan; Zhang, Shuang; Wu, Yingnan; Jia, Tianshuang; Yang, Xuan; Lee, Leo Tsz On; Sun, Litao
Abstract: Introduction: Hypertensive disorders of pregnancy(HDP) is a complex and challenging group of pregnancy complications that is one of the leading causes of maternal and fetal death worldwide. Recent studies have shown that the single nucleotide polymorphism(SNP) may play a role in the pathogenesis of HDP. This study aimed to investigate the association of MiR-146a rs2910164 and insulin receptor(INSR) rs2059806 SNPs with HDP and their associated complications in the Han population of Northeast China. Methods: A total of 240 HDP patients and 380 healthy controls were selected for genotype determination. For the most special and high incidence of HDP, we also studied the SNPs in association with pre-eclampsia(PE) patients. In addition, HDP complicated with gestational diabetes mellitus(GDM) patients was further analyzed to identify the association between SNPs and HDP-related complications. Multivariate logical regression analysis combined with 10, 000 permutation test corrections was used to analyze the association of MiR-146a and INSR SNPs with HDP. Results: After adjusting for relevant factors, MiR-146a rs2910164 or INSR rs2059806 SNPs were not significantly different between HDP or PE patients and healthy controls( P >0.05). Meanwhile, MiR146a rs2910164 and INSR rs2059806 SNPs were not significantly different between HDP complicated with GDM and control group. Discussion: Our data indicates that MiR-146a rs2910164 and INSR rs2059806 SNPs may not be significantly related with HDP in the Han population of Northeast China living in Heilongjiang Province. Highlights: HDP is a group of pregnancy complications that can cause maternal and infant death. Genetic factors play an important role in the pathogenesis of HDP. We discussed the relationship between MiR-146a and INSR SNPs and HDP in the Han population of Northeast China. MiR-146a and INSR SNPs may be unrelated to the HDP in the Han population of Northeast China.